Love-hate relationship between hepatitis B virus and type 2 diabetes: a Mendelian randomization study - Yu, Yunfeng; Tong, Keke; Hu, Gang; Yang, Xinyu; Wu, Jingyi; Bai, Siyang; Yu, Rong (Frontiers in Microbiology, 2024)
OBJECTIVE: The impact of hepatitis B virus (HBV) on the risk of type 2 diabetes (T2D) remains a controversial topic. This study aims to analyze the causal relationship between HBV and T2D using Mendelian randomization (MR). METHODS: Single nucleotide polymorphisms on chronic hepatitis B (CHB), liver fibrosis, liver cirrhosis, and T2D were obtained from BioBank Japan Project, European Bioinformatics Institute, and European Bioinformatics Institute. Mendelian randomization was utilized to evaluate exposure-outcome causality. Inverse variance weighting was used as the primary method for MR analysis. To assess horizontal pleiotropy and heterogeneity, we conducted MR-Egger intercept analysis and Cochran's Q test, and the robustness of the MR analysis results was evaluated through leave-one-out sensitivity analysis. RESULTS: MR analysis revealed that CHB was associated with a decreased genetic susceptibility to T2D (OR, 0.975; 95% CI, 0.962-0.989; p < 0.001) while liver cirrhosis (OR, 1.021; 95% CI, 1.007-1.036; p = 0.004) as well as liver cirrhosis and liver fibrosis (OR, 1.015; 95% CI, 1.002-1.028; p = 0.020) were associated with an increased genetic susceptibility to T2D. MR-Egger intercept showed no horizontal pleiotropy (p > 0.05). Cochran's Q showed no heterogeneity (p > 0.05). Leave-one-out sensitivity analysis showed that the results were robust. CONCLUSION: CHB has the potential to act as a protective factor for T2D, but its effectiveness is constrained by viral load and disease stage. This protective effect diminishes or disappears as viral load decreases, and it transforms into a risk factor with the progression to liver fibrosis and cirrhosis.